2022
DOI: 10.1155/2022/5335936
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Falsified Antimalarial Sulfadoxine-Pyrimethamine and Dihydroartemisinin-Piperaquine Drugs Using a Low-Cost Handheld Near-Infrared Spectrometer

Abstract: Falsified drugs are of serious concern to public health worldwide, particularly for developing countries where quality control of drugs is inefficient. In law enforcement against such fake medicines, there is a need to develop reliable, fast, and inexpensive screening methods. In this work, the ability of an innovative low-cost handheld near-infrared spectrometer to identify falsifications among two antimalarial fixed dose combination tablets, dihydroartemisinin/piperaquine and sulfadoxine/pyrimethamine, has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…These results are similar to those of Ciza et al who found that the application of OCC models to NIR spectra allowed a good discrimination between samples containing different APIs [43]. Moreover, these findings are in accordance with those of Yabre et al who achieved 100% specificity with correct discrimination of falsified samples [5,44].…”
Section: Plos Onesupporting
confidence: 91%
“…These results are similar to those of Ciza et al who found that the application of OCC models to NIR spectra allowed a good discrimination between samples containing different APIs [43]. Moreover, these findings are in accordance with those of Yabre et al who achieved 100% specificity with correct discrimination of falsified samples [5,44].…”
Section: Plos Onesupporting
confidence: 91%